PROGNOSIS OF REPARATIVE OSTEOGENESIS IN RATS WITH OPEN MANDIBULAR FRACTURE ON THE BACKGROUND OF OSTEOPOROSIS - Goltsev, A.M.; Lykhytskyi, O.O. (World of Medicine and Biology, 2018)
In this work, mathematical prediction of the course of reparative osteogenesis in rats with an open fracture of the mandible on the background of osteoporosis has been carried out. It is shown that important biochemical markers for prognosis of osteo-reparation processes under conditions of simulated pathology are the content of VEGF, TGF-β1, carbonyl groups of proteins, nitrites and nitrates in serum. Among these biochemical indicators, the greatest value for controlling the processes of reparative osteoregeneration is the determination of the content of TGF-β1 and VEGF in serum, but less important is the study of the level of carbonyl groups of proteins and nitrites and nitrates in serum.